Restorative Justice In The Criminal Justice System: An Analysis of Sentencing Proportionality in the Crime of Embezzlement in Office Involving Minor Losses (An Analysis of the Stabat District Court Decision Number 214/Pid.Sus/2025/PN Stb) - Muhammad Zakiri; Faisal; Tengku Erwinsyahbana (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study examines the application of restorative justice to the crime of embezzlement in office involving minor losses, through a case study of the Stabat District Court Decision Number 214/Pid.Sus/2025/PN Stb. The issues discussed encompass the qualification of criminal acts that meet the requirements for restorative resolution, the orientation of criminal law enforcement, and judicial considerations in sentencing. Employing a normative juridical method with statutory, case, and conceptual approaches, this study finds that embezzlement in office with a loss value below the threshold prescribed by Supreme Court Regulation Number 2 of 2012 qualifies as a minor offense and objectively meets the criteria for restorative justice. In the a quo decision, the judge imposed a 1 (one) year imprisonment sentence for a loss amounting to IDR 187,500.00. Resolution through restorative justice could not be implemented due to the absence of a settlement agreement from the victim. Nevertheless, the imposition of the custodial sentence is deemed to insufficiently reflect the principles of proportionality and legal utility. In this regard, the judge inherently possesses the authority to consider alternative sentencing options other than imprisonment, in alignment with the legal principle that positions imprisonment as an ultimum remedium.